(untitled) (Vietnam Journal of Community Medicine, 2026)
Background:Liver fluke infection caused by Opisthorchis viverrini is a parasitic disease closely associated with cholangiocarcinoma. In the Central Highlands of Viet Nam, the disease remains endemic; however, local epidemiological data are still limited. A rapid diagnostic test detecting O. viverrini antigen in urine (OV Antigen RDT) has shown potential for community-based screening. Objectives: (1) To determine the prevalence of O. viverrini infection using the Formalin–Ether Concentration Technique (FECT) in Dak Glei district (Kon Tum province) in 2025; (2) To preliminarily compare selected diagnostic performance indicators of the OV Antigen rapid test with FECT. Methods: A cross-sectional descriptive study combined with a diagnostic comparison study was conducted. A total of 403 individuals aged ≥5 years provided stool samples for FECT examination. For the diagnostic comparison, 49 FECT-positive cases and 40 FECT-negative samples were randomly selected for OV Antigen testing using urine specimens. FECT was used as the reference standard. Results: The prevalence of O. viverrini infection by FECT was 12.2% (49/403), with all infections classified as light (<1,000 eggs/g of stool) and a mean intensity of 49.15 ± 25.20 eggs/g. Infection prevalence was higher in males (18.2%; OR = 2.41), highest in the 16–59 age group (15.3%), and higher in Dak Mon commune (OR = 2.88). The OV Antigen rapid test showed a sensitivity of 100%, specificity of 75%, overall accuracy of 88.8%, and substantial agreement with FECT (Kappa = 0.77; p < 0.0001). Conclusions: O. viverrini infection remains prevalent in Dak Glei district. The OV Antigen rapid test demonstrated high sensitivity and good agreement with FECT, indicating its potential application for community screening and epidemiological surveillance in high-risk areas.